Conversion of fly ash - an environmentally detrimental waste to zeolite beta (BEA) for commercial catalytic applications - Kasture, M. W.; Bokade, Vijay V.; Joshi, P. N. (Journal of the American Ceramic Society, 2005)
Zeolite beta (BEA) was synthesized hydrothermally using fly ash as a combined source of alumina and silica. The overall crystallization period required to obtain pure crystalline BEA zeolite was found to be slightly longer when fly ash was used. The physicochemical properties of BEA phases obtained using fly ash (FLBEA) and conventional source materials (CONBEA) were compared. The H/FLBEA catalyst has exhibited excellent catalytic performance in commercially important benzene isopropylation process. These results have demonstrated that converting fly ash into BEA zeolite not only alleviates the disposal problem but also turns an otherwise waste material into a marketable commodity.

Catalytic upgrading of renewable levulinic acid to ethyl levulinate biodiesel using dodecatungstophosphoric acid supported on desilicated H-ZSM-5 as catalyst - Nandiwale, Kakasaheb Y.; Sonar, Shilpa K.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Patil, Vilas S.; Bokade, Vijay V. (Applied Catalysis A-General, 2013)
Levulinic acid (LA) is considered as a renewable platform chemical and can be used for the synthesis of variety of important fuels and chemicals. In particular, its esterification with ethanol produces ethyl levulinate (EL) would be green process, as it can be used as diesel miscible biofuel (DMB), preventing global warming by decreasing atmospheric CO2. This study explores the use of modified H-ZSM-5 by desilication viz.; DH-ZSM-5 and dodecatungstophosphoric acid (DTPA) loaded on DH-ZSM-5 for esterification of LA with ethanol aiming to EL. Different degree of desilication of H-ZSM-5 was performed by using aq. NaOH (0.2-1.5 M) at 338 K for 30 min and then DTPA was loaded on these desilicated H-ZSM-5 (DH-ZSM-5) support. H-ZSM-5, DH-ZSM-5 and DTPA on these DH-ZSM-5 samples were characterized by powder x-ray diffraction (XRD), N-2 adsorption-desorption, pyridine chemisorbed IR spectroscopy, Temperature Programmed Ammonia Desorption (TPAD). The increase in conversion of levulinic acid was observed from 28% to 94% with increase of DTPA loading from 0% to 15%. The increased LA conversion may be due to increase in total acidity from 43.14% to 84.31%. The use of DH-ZSM-5 as support for deposition of DTPA may be reported for the first time. The present work also extended to optimize process parameters such as DTPA loading on DH-ZSM-5, catalyst to LA ratio, LA to ethanol molar ratio, speed of agitation, particle size reaction temperature and catalyst reusability. Kinetic study based on pseudo-homogeneous (P-H) model is also presented. The experimental results follow second order kinetics. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: desilicated H-ZSM-5; DTPA on desilicated H-ZSM-5; Esterification; ethyl levulinate; levulinic acid

Catalytic upgrading of citric acid to environmental friendly tri-butyl citrate plasticizer over ultra stable phosphonated Y zeolite - Nandiwale, Kakasaheb Y.; Gogoi, Pranjal; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
The catalytic synthesis of non-toxic/eco-friendly tributyl citrate (TBC) plasticizer by esterification of renewable citric acid (CA) with butanol would be completely sustainable route. In this context, catalytic performance of parent ultra stable Y (USY) and phosphonated USY catalysts were investigated for TBC synthesis. Parent USY and phosphonated USY catalysts were characterized by powder X-ray diffraction (XRD), N-2 adsorption-desorption, NH3 temperature programmed desorption (TPD), pyridine-Fourier Transform Infrared Spectroscopy (FTIR), FTIR, SEM, ICP. The influence of various process parameters such as phosphorous (P) loading (0 to 4 wt/%), catalyst loading (5-25%), molar ratio of CA to n-butanol (1:4 to 1:12), reaction temperature (383-423 K) and reaction time (1-5 h) have been investigated over USY catalyst with aim to maximize CA conversion and TBC yield. Amongst the studied catalysts, the 2% (w/w) P/USY was found to be highly potential catalyst with complete CA conversion (100%) and 93% TBC yield. The present method of using 2% (w/w) P/USY catalyst for the synthesis of TBC would be environmentally benign in the context of bio-renewable synthetic route, high catalytic activity, non-toxic product, long term stability and reusability of catalyst (five catalytic cycles). (c) 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved,
Keywords: Butanol; Citric acid; heterogeneous catalysis; Plasticizer; Tributyl citrate

Carbon supported size-controlled ru catalysts for selective levulinic acid hydrogenation into γ-valerolactone - Simakova, Irina L.; Demidova, Yuliya S.; Simonov, Mikhail N.; Niphadkar, Prashant S.; Bokade, Vijay V.; Devi, Nandini; Dhepe, Paresh L.; Murzin, Dmitry Yu (Journal of Siberian Federal University-Chemistry, 2020)
Liquid phase levulinic acid hydrogenation into γ-valerolactone in 1,4-dioxane as a solvent (165°C, 20 bar) was studied over a range of Ru monometallic catalysts using mesoporous carbon material Sibunit as a support. In addition to the catalyst prepared by impregnation with RuCl3∙nH2O (0.1 M) followed by reduction in H2, size-controlled Ru(NPs)/Sibunit catalysts were synthesized by immobilization of polyvinylpyrrolidone (PVP) stabilized Ru nanoparticles (NPs) (dRu=2.4 nm). Сarbon supported colloidal Ru NPs were not studied earlier in levulinic acid hydrogenation. Activity of colloidal Ru(NPs)/Sibunit catalysts was found to be lower than that of impregnated Ru/Sibunit which could be attributed to hampering effect of PVP. However, colloidal Ru(NPs)/Sibunit purified by thermal treatment in air (180°C) followed by reduction in H2 (400°C) exhibited the same activity as impregnated one yielding 93% γ-valerolactone at 100% levulinic acid conversion. Applicability of supported PVP-assisted colloidal Ru NPs in hydrogenation of levulinic acid illustrates a potential to prepare more efficient catalysts for this reaction with a desired particle size. The catalysts were characterized by TEM, XRF, and N2 physisorption to compare their physical chemical properties.

Catalytic activity of CuFe2O4 spinel oxide for liquid-phase oxidation of cinnamyl alcohol - Dange, Rutvija M.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (ChemistrySelect, 2022)
CuFe2O4 spinel oxide catalyst was synthesized by sol-gel and co-precipitation methods for liquid phase oxidation of Cinnamyl alcohol (CnOH) to Cinnamaldehydes (CnHO) using tert-Butyl hydroperoxide (TBHP) as oxidising agent. Spinel oxide catalyst was characterized by different techniques such as X-ray diffraction (XRD), N-2 adsorption-desorption, BET surface area, and X-ray photoelectron spectroscopy (XPS) to understand the structural, physical properties and oxidation state of the catalyst. The result shows that catalyst prepared by sol-gel method was found higher surface area and smaller crystalline size than co-precipitation method. XPS data confirm the formation of Cu2+ in the spinel which helps to improve the catalytic activity of oxidation. This reaction follows radical mechanism, and exhibited 76.7 % of CnOH conversion and 68.4 % of CnHO, and 24.8 % benzaldehyde (benzald) selectivity using TBHP at 60 degrees C. Kinetic data reveal that 41.2 kJ/mol of activation energy for the reaction. The higher activity of spinel oxide catalyst could be due synergetic effect of spinel (88 %) and oxides (12 %) formed in the catalyst, which helps to provide the oxygen during reaction. The contribution of Cu2+ is higher in sol-gel than co-precipitation, which may provide the better reactivity of catalyst. This work helps to select the effective and cost-effective catalyst for the oxidation of CnOH.
Keywords: Catalysts; Cinnamaldehyde; Cinnamyl Alcohol; Cupper; iron; oxide; spinel